Clinical indications for image-guided interventional procedures in the musculoskeletal system: a Delphi-based consensus paper from the European Society of Musculoskeletal Radiology (ESSR)-part VII, nerves of the lower limb - Sconfienza, Luca Maria; Adriaensen, Miraude; Albano, Domenico; Alcala-Galiano, Andrea; Allen, Georgina; Aparisi Gómez, Maria Pilar; Aringhieri, Giacomo; Bazzocchi, Alberto; Beggs, Ian; Chianca, Vito; Corazza, Angelo; Dalili, Danoob; et al. (Springer Science and Business Media LLC, 2022)
To perform a Delphi-based consensus on published evidence on image-guided interventional procedures for peripheral nerves of the lower limb (excluding Morton's neuroma) and provide clinical indications.
Keywords: Interventional radiology; Ultrasonography; Nerves; Lidocaine; Corticosteroid